Micellization behavior of 12-4-12 Gemini surfactant with sucrose and ribose: Thermodynamic insights and self-aggregation dynamics - Sharma, Nidhi; Sood, Sumita; Rashid, Rzgar Farooq; Saidani, Taoufik; Abdelmohsen, Shaimaa A.M.; Khan, M.Ijaz (Journal of the Indian Chemical Society, 2025)
In the current research, attempt has been made to evaluate the interactionsof 12-4-12 Gemini surfactanti.e. (butanediyl-1, 4-bis (dimethyldodecylammonium bromide) with sucrose and ribose to determine their self-aggregation behavior by evaluating the critical micelle concentration (CMC) through conductivity and spectrophotometric techniques. Reduction in CMC value of Gemini surfactant subject to carbohydrates was observed in the order: pure water > ribose > sucrose. Decrease in CMC values was more pronounced in case of sucrose, as compared to that of ribose which has been attributed to hydrophobicity difference between these sugars. Further, to understand the process of micellization, different thermodynamic variables viz. standard Gibbs free energy (ΔGm0), standard enthalpy (ΔHm0) and standard entropy (ΔSm0) of micellization were determined through pseudo phase separation model after studying the temperature dependent behavior of CMC. Thermodynamic parameters revealed that binding interactions between Gemini surfactant and carbohydrates were electrostatic and hydrophobic in nature, although hydrophobic interactions were more dominant at higher temperature. These finding suggest the suitability of Gemini Surfactant in stabilization of emulsions and biological applications. [Display omitted] •CMC reduction order: Pure water > ribose > sucrose.•Pronounced CMC decrease with sucrose vs ribose.•Hydrophobic interactions dominate at higher temperatures.•Electrostatic and hydrophobic interactions govern micellization.•Gemini surfactant suitable for emulsions, biological applications.